Gender and age structure of mortality caused by COVID-19 - Korkhmazov, V. T.; Alekseenko, S. N.; Perkhov, V. I. (Innovacionnaâ medicina Kubani (Online), 2022)
Introduction: The policy of mortality decline of the population of Russia, pursued by the state, requires consideration of the regional peculiarities of mortality in territorial subjects of the Russian Federation by gender and age. The regional situation on male and female mortality also should be considered when developing the measures directed to prevent various diseases including infectious ones. In this regard, the studies of gender and age indicators of mortality during the periods of infectious pandemics become relevant. Objective: The analysis of gender and age rates of COVID-19 mortality in 2021 in order to substantiate the best management decisions in the sphere of the organization of medical care and statistical registration of lethal outcomes during the pandemic spread of dangerous viral infections. Material and methods: The main source of information on mortality in 2020 is data of the State Statistics of Mortality of Rosstat. The data on mortality in 2021 are presented in the records on death cases in Federal State Information System “Unified State Register of Registration of Acts of Current State”. To evaluate the obtained data, simple (unweighted) arithmetic mean values, specific indicators, a root mean square (standard) deviation of the mean values, coefficient of variation were used (a measure of the spread of attribute values – the ratio of a standard deviation to the arithmetic-mean). Results: In 2021 17.3% of total number of all deaths had COVID-19 as an initial cause of death. 248,134 cases of those were women (58.5%), 176,116 cases were men (41.5%). The mortality rate from COVID-19 increased by an average 1.7 times upon transition from one five-year-old age group to another, 85% of those who died from COVID-19 were aged 60 years and older. In 2021 the coronavirus infection of COVID-19 contributed significantly to female mortality more, than male mortality, which is inconsistent with the data on gender structure of COVID-19 mortality in other countries, as well as with the widespread belief that men are more vulnerable to this infection. Conclusions: Growth rates of COVID-19 mortality depending on age resembles the aging rate, reflecting the biological nature of mortality. Total excess mortality is the better basis for assessment of changes in the population health during pandemics, than mortality from COVID-19 alone. The organization of systematic checks of correctness of coding the causes of death at the state registration of death is necessary. Restrictions: Data of the Federal State Information System “Unified State Register of Registration of Acts of Current State” can differ from data of Rosstat which in 2022 became available to professional researchers later, than data of the Federal State Information System “Unified State Register of Registration of Acts of Current State”.